TEACHING YESTERDAY AND TODAY BETWEEN BEING LOVED AND BEING FEARED: THE PROBLEM OF AUTHORITY - Elvis Rezende MESSIAS; André Luiz Sena MARIANO (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article aims to reflect on the problem of authority inherent in the teaching activity. The reflection of theoretical reference currents and different historical periods, in a nonlinear approach. The focus is in the tension between being loved and being feared and often difficult to decide between them. However, it questioned the real need for this choice, aiming to think the authority as a service to the true otherness and autonomy.